Human and Mouse Gene Structure: Comparative Analysis and Application to Exon Prediction - Batzoglou, Serafim; Pachter, Lior; Mesirov, Jill P.; Berger, Bonnie; Lander, Eric S. (Genome Research, 2000)
We describe a novel analytical approach to gene recognition based on cross-species comparison. We first undertook a comparison of orthologous genomic loci from human and mouse, studying the extent of similarity in the number, size and sequence of exons and introns. We then developed an approach for recognizing genes within such orthologous regions by first aligning the regions using an iterative global alignment system and then identifying genes based on conservation of exonic features at aligned positions in both species. The alignment and gene recognition are performed by new programs calledGLASS and ROSETTA, respectively.ROSETTA performed well at exact identification of coding exons in 117 orthologous pairs tested.